2005
DOI: 10.1007/s11205-004-2211-x
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Moderated Model of Satisfaction with Urban Living using Data for Brisbane-South East Queensland, Australia

Abstract: community satisfaction, housing satisfaction, life satisfaction, neighbourhood satisfaction, path analysis, perception, quality of life, regional satisfaction, survey research,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 23 publications
5
94
0
2
Order By: Relevance
“…For example, McCrea et al (2005) investigated quality of life and the subjective evaluations of it at a different spatial level. He found regional services such as access to health and higher education services gained the highest satisfaction at a regional level while neighborhood satisfaction was found to be associated with social interactions, crime and urban amenities such as K-12 schools, parks and libraries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, McCrea et al (2005) investigated quality of life and the subjective evaluations of it at a different spatial level. He found regional services such as access to health and higher education services gained the highest satisfaction at a regional level while neighborhood satisfaction was found to be associated with social interactions, crime and urban amenities such as K-12 schools, parks and libraries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…En tal sentido, se ha analizado la forma en que las condiciones físicas, sociales y económicas de la colonia influyen en la satisfacción con ésta, lo que a su vez determina el nivel de satisfacción con la vida (Salleh y Badarulzaman, 2012;Miller et al, 1980); también ha sido importante determinar cómo el grado de satisfacción es un factor que influye en las decisiones de mudarse de los residentes (Clark et al, 2006;Brower, 2003;Droettboom et al, 1971;Kasl y Harburg, 1972;Lee et al, 1994;Nathanson et al, 1976;Newman y Duncan, 1979;Quigley y Weinberg, 1977); en el nivel o calidad de vida (Campbell et al, 1976;Sirgy et al, 2000;McCrea et al, 2005;Sirgy y Cornwell, 2002;Parkes et al, 2002), así como en la educación que reciben los hijos en el hogar (Martinez et al, 2002). Se ha reconocido que los residentes que experimentan mayor satisfacción con su colonia reportan mejor salud mental, perciben menos inseguridad y muestran una menor probabilidad de mudarse (Baba y Austin, 1989;Adams, 1992;Bolan, 1997;Sirgy y Cornwell, 2002;Austin et al, 2002;Oh, 2003).…”
Section: Literatura En Torno a La Satisfacción Con La Coloniaunclassified
“…McCrea et al [30] examined different geographic levels of subjective urban QOL. Regional satisfaction was best predicted by evaluations of regional services (such as health and education) and the cost of living, while evaluations of environmental and urban growth problems were significant predictors of regional satisfaction for younger persons.…”
Section: Intruductionmentioning
confidence: 99%
“…Objective urban QOL studies typically include many objective characteristics of the urban environment, often combining or weighting objective indicators to generate an objective urban QOL ranking for places [2,3,6,43,48,50] . Studies on subjective urban QOL have found that subjective evaluations of many aspects of the urban environment can contribute to satisfaction in urban domains and overall life satisfaction [30,33,45,46,49] . The urban quality of life is measured by using the subjective indicators and instead of secondary data, the citizens are asked (questionnaires, interview…) directly for the level of their happiness about different aspects of urban life.…”
Section: Measuring Quality Of Lifementioning
confidence: 99%